FROM ACTION STRATEGY TO NEW UZBEKISTAN: STRENGTHENING THE SOCIO-POLITICAL POSITION OF WOMEN (Scientific journal of the Fergana State University, 2026)
This article provides a comprehensive analysis of measures aimed at strengthening the socio-political position of women within the framework of the Action Strategy for the period of large-scale reforms in Uzbekistan for 2017–2021 and the subsequent Development Strategy of New Uzbekistan. The article analyzes the quantitative increase in political participation as a result of the introduction of the Law "On Guarantees of Equal Rights and Opportunities for Women and Men" and gender quotas, which guarantees women's rights. It also examines the role of the "Women's Notebook" system in attracting women to economic activity and public work, in addition to social protection. In conclusion, the article develops scientifically based practical proposals for qualitatively strengthening the position of women, in particular, for the systematic training of political reserve individuals, increasing economic independence and strengthening gender sensitivity.